2020
DOI: 10.1155/2020/3896754
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Epidemiological Investigation of Paratuberculosis in Dairy Cattle in Tai’an, China

Abstract: Paratuberculosis, a chronic and sometimes fatal disease of ruminants, is caused by Mycobacterium avium subsp. paratuberculosis (MAP). In this study, we examined paratuberculosis cases among 2–4-year-old dairy cows at farms in Shandong Province, China. Paratuberculosis cases were diagnosed based on clinical symptoms, pathological autopsy, and histopathological inspection. Characteristics of paratuberculosis in the affected dairy cattle included poor body condition, persistent diarrhea, subcutaneous edema, granu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…However, different regions had a different prevalence. In northern and northeastern China, the seroprevalence of MAP was 11.79%, with a 20.35% herd-level seroprevalence; in Shandong Province, the herd prevalence was about 60%, and the animal level was around 10% [15,16]; and in Inner Mongolia, the prevalence was 10.79%, based on serum tests [17]. This highlights the widespread nature of the disease within dairy cattle populations and underscores the urgent need for effective control and management strategies in China.…”
Section: Introductionmentioning
confidence: 92%
“…However, different regions had a different prevalence. In northern and northeastern China, the seroprevalence of MAP was 11.79%, with a 20.35% herd-level seroprevalence; in Shandong Province, the herd prevalence was about 60%, and the animal level was around 10% [15,16]; and in Inner Mongolia, the prevalence was 10.79%, based on serum tests [17]. This highlights the widespread nature of the disease within dairy cattle populations and underscores the urgent need for effective control and management strategies in China.…”
Section: Introductionmentioning
confidence: 92%
“…The study has shown that the overall MAP seroprevalence in the tested Tibetan sheep was 11.29% (12). Recent studies showed that paratuberculosis was widely prevalent in dairy farms in Tai'an, Shandong Province (13). Therefore, more attention should be paid to the epidemic prevention and control of paratuberculosis.…”
Section: Introductionmentioning
confidence: 99%
“…The symptoms include diarrhea, progressive weight loss, and decreased milk production. Affected animals usually die after suffering cachexia and dehydration [ 2 , 3 ]. A long subclinical phase with probable intermittent shedding before the high shedding clinical phase is among the significant characteristics of this disease in cows [ 4 ].…”
Section: Introductionmentioning
confidence: 99%